Post-fire carbon and nitrogen accumulation and succession in Central Siberia. Issue 1 (December 2017) - Larjavaara, Markku; Berninger, Frank; Palviainen, Marjo; Prokushkin, Anatoly; Wallenius, Tuomo
Abstract Improved understanding of carbon (C) accumulation after a boreal fire enables more accurate quantification of the C implications caused by potential fire regime shifts. We coupled results from a fire history study with biomass and soil sampling in a remote and little-studied region that represents a vast area of boreal taiga. We used an inventory approach based on predefined plot locations, thus avoiding problems potentially causing bias related to the standard chronosequence approach. The disadvantage of our inventory approach is that more plots are needed to expose trends. Because of this we could not expose clear trends, despite laborious sampling. We found some support for increasing C and nitrogen (N) stored in living trees and dead wood with increasing time since the previous fire or time since the previous stand-replacing fire. Surprisingly, we did not gain support for the well-established paradigm on successional patterns, beginning with angiosperms and leading, if fires are absent, to dominance ofPicea . Despite the lack of clear trends in our data, we encourage fire historians and ecosystem scientists to join forces and use even larger data sets to study C accumulation since fire in the complex Eurasian boreal landscapes.